2012
DOI: 10.5604/15093492.1005083
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Randomized Controlled Trials Comparing Efficacy of Crossed Versus Lateral K-wire fixation in Extension type Gartland type III Supracondylar Fractures of the Humerus in Children

Abstract: Supracondylar fractures of the humerus occur frequently in children and account for approximately 70% of all elbow fractures. The aim of this systematic review is to critically appraise randomized controlled trials in the literature comparing the outcome of surgical treatment of extension type Gartland III supracondylar fractures using either a cross pin configuration or lateral pins only for fixation in terms of the stability of fixation and the incidence of encountered complications. Only 4 randomized trials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 44 publications
3
16
1
2
Order By: Relevance
“…These results are consistent with previous literature. 12,14,16 In our study, the fractures are more common on left side as observed i.e. 58% in total of patients (60% in group 1 and 56% in group 2).…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…These results are consistent with previous literature. 12,14,16 In our study, the fractures are more common on left side as observed i.e. 58% in total of patients (60% in group 1 and 56% in group 2).…”
Section: Discussionsupporting
confidence: 54%
“…These results were also more common in previous studies. 14,16,17 In the present study, 72% of total cases had mode of injury as fall from height among group 1, as compared to 64% among group 2. Remaining cases had injury because of fall from bicycle, fall from bike and fall while playing, all these mode of injury involved mechanism of fall from height with extended elbow.…”
Section: Discussionmentioning
confidence: 41%
See 1 more Smart Citation
“…Supracondylar fractures of the humerus in children are more common under the age of 10. In particular, incidence peaks between the ages of 5–7 have been reported [46]. In our series, the age distribution is from 2 to 14.…”
Section: Discussionsupporting
confidence: 49%
“…Surgical procedures are the treatment of choice in displaced supracondylar humerus fractures [2]. Humerus fractures are a significant part of pediatric fractures due to high incidence, high morbidity, and serious complications [3, 4]. …”
Section: Introductionmentioning
confidence: 99%